Pair interactions between conducting and non-conducting cylinders under uniform electric field. (13th March 2016) - Feng, Huicheng; Wong, Teck Neng
Abstract: This paper analytically studies pair interactions between a conducting and a non-conducting cylinder with uniform electric fields imposed in two basic ways: perpendicular and parallel to the connection line of the two cylinder centers. The results show that electroosmosis and induced charge electroosmosis are generated on the non-conducting and conducting cylinders, respectively. Moreover, the nonuniform local electric field and the corresponding asymmetric fluid flow drive the cylinders into motion: both translating and rotating under the perpendicular applied electric field, while solely migrating along the x -axis under the parallel applied electric field. The velocity component due to electrostatic force is negligible compared to that due to electrophoresis or induced charge electrophoresis. Since the pair interactions reduce as the distance between cylinders increases, the cylinder velocities decrease accordingly. Under the perpendicular applied electric field, the cylinders repel each other along the x -axis; the motion direction along the y -axis as well as the direction of rotational velocity depends on the sign of the zeta potential of non-conducting cylinder. Under the parallel applied electric field, the cylinders repel each other when the zeta potential of non-conducting cylinder is positively very small or negative, while they attract each other when the zeta potential is positively large. Abstract : Highlights: An analytical model of pair interactions between a conducting and a non-conducting cylinder under uniform electric fields is established. Electroosmosis and induced charge electroosmosis around cylinders are captured. Cylinder translation and rotation due to pair interactions are characterized.